2022
DOI: 10.5194/tc-16-219-2022
|View full text |Cite
|
Sign up to set email alerts
|

Proper orthogonal decomposition of ice velocity identifies drivers of flow variability at Sermeq Kujalleq (Jakobshavn Isbræ)

Abstract: Abstract. The increasing volume and spatio-temporal resolution of satellite-derived ice velocity data have created new exploratory opportunities for the quantitative analysis of glacier dynamics. One potential technique, proper orthogonal decomposition (POD), also known as empirical orthogonal functions, has proven to be a powerful and flexible technique for revealing coherent structures in a wide variety of environmental flows. In this study we investigate the applicability of POD to an openly available TanDE… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 68 publications
2
17
2
Order By: Relevance
“…4.1.2 Role of higher-order modes EOF/PC decomposition of three years of glacier speed data in a 2.5 × 4 km area on Jakobshavn Isbrae by Ashmore et al (2021) revealed similar results as we find here: a strong first mode (98%) followed by higher-order modes with coherent spatial and temporal patterns. However, Ashmore et al (2021) discovered that modes 2 and 3 were paired:…”
Section: Benefits Of Eof Analysis Over Single-point Analysissupporting
confidence: 81%
See 4 more Smart Citations
“…4.1.2 Role of higher-order modes EOF/PC decomposition of three years of glacier speed data in a 2.5 × 4 km area on Jakobshavn Isbrae by Ashmore et al (2021) revealed similar results as we find here: a strong first mode (98%) followed by higher-order modes with coherent spatial and temporal patterns. However, Ashmore et al (2021) discovered that modes 2 and 3 were paired:…”
Section: Benefits Of Eof Analysis Over Single-point Analysissupporting
confidence: 81%
“…The leading modes (highest variance explained) often, but are not mathematically required to, represent a distinct phenomenon that gives rise to a unique spatio-temporal pattern. For example, the Arctic Oscillation is the first mode of the wintertime sea-level pressure field in the northern hemisphere (Lorenz, 1951;Thompson & Wallace, 1998), and the first mode of ice flow speed in a specific area of Jakobshavn Isbrae captures the effects of seasonal stress changes at the glacier terminus (Ashmore et al, 2021).…”
Section: Eof/pc Decompositionmentioning
confidence: 99%
See 3 more Smart Citations